Comparative study of hand sewn single layer anastomosis of dog's bowel Estudo comparativo das anastomoses manuais em plano único do intestino delgado de cães - João Luiz Moreira Coutinho Azevedo; Octávio Hypólito; Otávio Cansanção Azevedo; Otávio Monteiro Becker Jr.; Dalmer Faria Freire (Arquivos de Gastroenterologia, 2008)
BACKGROUND: Two-layer intestinal anastomosis increases the inflammatory response while single-layer anastomosis results in a better wound healing. However the four main kinds of stitches which may be chosen in performing single layer intestinal sutures never before had been comparatively studied. AIM: To compare the four more commonly used types of single layer surgical anastomosis sutures of the digestive tract. METHODS: Six mongrel dogs were operated, each one receiving two anastomosis: one at 30 cm from de Treitz angle - sero-submucosal technique, and the other at 60 cm - total technique. This placement was alternatively inverted. The four more commonly used types of single layer surgical anastomosis sutures of the digestive tract, namely: sero-submucosal stitches tied in the lumen, over the submucosa; sero-submucosal stitches tied in the exterior of the organ, over the serosa; total stitches tied in the lumen, over the mucosa; and total sutures tied in the exterior, over the serosa (Gambee's stitches) were tested. After euthanasia (7th post-operative day) macro and microscopic features were evaluated. Friedman's test was applied for morphometry and for evaluation of the peritoneal adhesions. RESULTS: Statistical significance was demonstrated through major residual acute inflammation and proliferation in total sutures and more profuse adhesions with the sero-submucosal stitches tied in the lumen. The sero-submucosal stitches tied in the exterior over the serosa, had excellent realignment and regeneration of the layers. CONCLUSION: The sero-submucosal stitches tied in the exterior, over the serosa, were the best ones. RACIONAL: As anastomoses intestinais em dois planos aumentam a resposta inflamatória tecidual, enquanto que a anastomose em plano único resulta em um lúmen maior com menos danos às bordas teciduais. Entretanto, os quatro tipos de suturas mais comumente utilizados em suturas intestinais nunca foram antes estudados comparativamente. OBJETIVO: Comparar os quatro tipos de sutura do tubo digestivo em plano único mais freqüentemente utilizados para anastomoses manuais do tubo digestivo. MÉTODOS: Seis cães de raça indefinida foram operados, cada um recebendo duas anastomoses: uma a 30 cm do ângulo de Treitz - técnica sero-submucosa, e a outra a 60 cm - técnica total. Esta localização foi aleatoriamente invertida. Os quatro tipos de sutura em plano único mais freqüentemente utilizados para anastomoses manuais do tubo digestivo, denominados: pontos extramucoso atados no lúmen da víscera, sobre a submucosa, pontos extramucosos atados no exterior, sobre a serosa, pontos totais atados no lúmen, sobre a mucosa, e pontos totais especiais de Gambee atados no exterior sobre a serosa, foram testados. Eutanásia e necropsia parcial no 7º dia pós-operatório permitiu avaliação de aspectos macro e microscópicos. O teste de Friedman's foi aplicado para a morfometria e avaliação das aderências peritoniais. RESULTADOS: Foi demonstrada diferença estatisticamente significante para a inflamação residual aguda e maior proliferação nas suturas totais, bem como na maior ocorrência de aderências com pontos extramucosos atados no lúmen da víscera, sobre a submucosa. A sutura extramucosa com nós atados na serosa teve regeneração das bordas e alinhamento excelentes. CONCLUSÃO: A sutura extramucosa com nós atados na serosa mostrou-se a melhor.